1998
DOI: 10.1111/j.1469-7793.1998.415bw.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of calcium signals by intracellular pH in isolated rat pancreatic acinar cells

Abstract: We have investigated the interactions between intracellular pH (pHi) and the intracellular free calcium concentration ([Ca2+]i) in isolated rat pancreatic acinar cells. The fluorescent dyes fura‐2 and BCECF were used to measure [Ca2+]i and pHi, respectively. Sodium acetate and ammonium chloride (NH4Cl) were used to acidify and alkalinize pHi, respectively. Cytosolic acidification had no effect on [Ca2+]i in resting pancreatic acinar cells, whereas cytosolic alkalinization released Ca2+ from intracellular store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 51 publications
5
50
0
Order By: Relevance
“…] i changes in response to pH e changes Based on previous studies in trout hepatocytes (Walsh, 1986;Krumschnabel et al, 2001b) e , which is consistent with observations in smooth muscle cells (Siskind et al, 1989), rat pheochromocytoma cells (Dickens et al, 1989), bovine lactotrophs (Zorec et al, 1993), rat lacrimal (Yodozawa et al, 1997) and pancreatic acinar cells (Speake and Elliott, 1998) but not with those in rat lymphocytes (Grinstein and Goetz, 1985) ] i (Grinstein and Goetz, 1985 e inhibited this mechanism, resulting in a slower pHi recovery (Fig.·6A). Looking at the peak of pHi increase in response to NH 4 Cl exposure, the difference between the control treatment, on the one hand, and the absence of Ca e was recorded in rat pheochromocytoma cells (Dickens et al, 1989) and vascular smooth muscle (Dickens et al, 1989;Batlle et al, 1993) while no effect on [Ca 2+ ] i has been reported in toxoplasma gondii tachyzoites (Moreno and Zhong, 1996) and rat pancreatic acinar cells (Speake and Elliott, 1998).…”
Section: +supporting
confidence: 88%
See 1 more Smart Citation
“…] i changes in response to pH e changes Based on previous studies in trout hepatocytes (Walsh, 1986;Krumschnabel et al, 2001b) e , which is consistent with observations in smooth muscle cells (Siskind et al, 1989), rat pheochromocytoma cells (Dickens et al, 1989), bovine lactotrophs (Zorec et al, 1993), rat lacrimal (Yodozawa et al, 1997) and pancreatic acinar cells (Speake and Elliott, 1998) but not with those in rat lymphocytes (Grinstein and Goetz, 1985) ] i (Grinstein and Goetz, 1985 e inhibited this mechanism, resulting in a slower pHi recovery (Fig.·6A). Looking at the peak of pHi increase in response to NH 4 Cl exposure, the difference between the control treatment, on the one hand, and the absence of Ca e was recorded in rat pheochromocytoma cells (Dickens et al, 1989) and vascular smooth muscle (Dickens et al, 1989;Batlle et al, 1993) while no effect on [Ca 2+ ] i has been reported in toxoplasma gondii tachyzoites (Moreno and Zhong, 1996) and rat pancreatic acinar cells (Speake and Elliott, 1998).…”
Section: +supporting
confidence: 88%
“…Looking at the peak of pHi increase in response to NH 4 Cl exposure, the difference between the control treatment, on the one hand, and the absence of Ca e was recorded in rat pheochromocytoma cells (Dickens et al, 1989) and vascular smooth muscle (Dickens et al, 1989;Batlle et al, 1993) while no effect on [Ca 2+ ] i has been reported in toxoplasma gondii tachyzoites (Moreno and Zhong, 1996) and rat pancreatic acinar cells (Speake and Elliott, 1998). In the present study, exposure of trout hepatocytes to the weak acid Na-propionate induced a slow increase in [Ca 2+ ] i .…”
Section: +mentioning
confidence: 96%
“…Therefore, we directly visualized the change in pH i in naive (nontransfected) EA.hy cells after 3OC12 treatment by laser scanning confocal microscopy. Because decreased pH i can induce Ca 2ϩ release and because increased cytosolic Ca 2ϩ [(Ca 2ϩ ) c ] is a common response to 3OC12 in mammalian cells (8,34), we also concomitantly measured [Ca 2ϩ ] c fluxes. The cells were simultaneously loaded with the Ca 2ϩ indicator Fluo-4 AM and the ratiometric pH indicator SNARF-4F and treated with 3OC12, and time-lapse images were acquired.…”
Section: Pon2 Mediates Intracellular 3oc12 Acid Accumulationmentioning
confidence: 99%
“…Acinar Cell Isolation-Small clusters of rat pancreatic acinar cells were isolated by enzymatic digestion of the pancreas with collagenase as described previously (13,14), except that all media contained a reduced concentration of CaCl 2 (0.5 mM). This value, which is less than half the physiological concentration, was selected to avoid possible activation of CaRs, which is known to occur at [Ca 2ϩ ] concentrations of 1 mM and above (2).…”
Section: Reverse Transcriptase-pcr (Rt-pcr)-malementioning
confidence: 99%